Gradenigo’s Syndrome and Labyrinthitis: Conservative versus Surgical Treatment - Ahmad Al-juboori; Amira Nasser Al Hail (Case Reports in Otolaryngology)
Background. Extracranial intratemporal complications of chronic suppurative otitis media (CSOM) are extremely rare. Gradenigo’s syndrome is defined as a clinical triad of otitis media, severe pain originating from the trigeminal nerve, and ipsilateral sixth cranial nerve palsy. Case Report. A 61-year-old man presented with chronic left ear discharge, left-sided headache, diplopia associated with vertigo, tinnitus, and hearing impairment. MRI with contrast showed asymmetrical signal changes in the bilateral petrous bone with reduced enhancement on the left with high suspicion of petrositis; in the context of chronic tympanomastoiditis, there was a 10 × 4 mm enhancing lesion in the left internal auditory meatus involving the 7th-8th nerve complex. The patient was treated conservatively with local and systemic antimicrobial agents, he had satisfactory response and improvement regarding symptoms of ear discharge, vertigo, and diplopia, but there is no remarkable response regarding hearing loss and tinnitus. Conclusion. Although there is little evidence to support the use of conservative treatment in the treatment of Gradenigo’s syndrome resulting from chronic ear disease, we here demonstrate successful conservative treatment of Gradenigo’s syndrome.